Search for quark contact interactions and extra spatial dimensions using dijet angular distributions in proton-proton collisions at root s=8 TeV - (:unkn) unknown (ELSEVIER, 2015)
A search is presented for quark contact interactions and extra spatial dimensions in proton-proton collisions at root s = 8 TeV using dijet angular distributions. The search is based on a data set corresponding to an integrated luminosity of 19.7 fb(-1) collected by the CMS detector at the CERN LHC. Dijet angular distributions are found to be in agreement with the perturbative QCD predictions that include electroweak corrections. Limits on the contact interaction scale from a variety of models at next-to-leading order in QCD corrections are obtained. A benchmark model in which only left-handed quarks participate is excluded up to a scale of 9.0 (11.7) TeV for destructive (constructive) interference at 95% confidence level. Lower limits between 5.9 and 8.4 TeV on the scale of virtual graviton exchange are extracted for the Arkani-Hamed-Dimopoulos-Dvali model of extra spatial dimensions. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; QCD; Electroweak corrections; Contact interactions; Extra dimensions; HADRON-HADRON COLLISIONS; TO-LEADING ORDER